Implementation and Monitoring of Hazard Analysis Critical Control Points In The of Main Course Chicken Red Curry For Ek Airline In PT. AID - Sang Ayu Made Agung Prasetiawati Djelantik; Anak Agung Made Semariyani; Ni Made Ayu Suardani Singapurwa (SEAS (Sustainable Environment Agricultural Science), 2025)
Food is an important component in maintaining health and meeting energy needs, including in long-haul flight services. One important aspect of aviation is the provision of food through PT AID's in-flight catering service. AID is an aviation catering service provider that has been certified with ISO 9001 and ISO 22000 and implements a quality management system and food safety based on GMP, SSOP, and HACCP. This study aims to assess the application of the HACCP system in ensuring the quality and safety of Chicken Red Curry products served to economy class airline passengers. The application of HACCP is carried out through the identification of five Critical Control Points (CCP), namely CCP 1 (receiving chilled and frozen raw materials), CCP 2 (chilled and frozen storage), CCP 3 (cooking process), CCP 4 (blast chilling), and CCP 5 (portioning and serving). The production process also includes the stages of receiving, storage, thawing, cooking, blast chilling, portioning, meal tray set-up, final holding, and delivery to the aircraft. The implementation of a comprehensive HACCP system at every stage of production aims to minimize the risk of physical, chemical, and microbiological contamination and maintain the organoleptic quality of products such as taste, aroma, color, and texture. With strict quality control, PT AID is able to guarantee the safety and quality of food products served on flights, thereby increasing consumer satisfaction and trust.